2004
DOI: 10.3402/ijch.v63i0.17944
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of sexual violence and relocation in the lives of HIV infected Canadian women

Abstract: Early intervention programs must be implemented in partnership with communities to reduce family violence and create support networks for children, youth and adults at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…Our study does have a number of limitations. First, our childhood adversity measure does not contain an item specific to sexual abuse, a critically important adverse childhood experience known to be more prevalent in women, MSM, and people who use drugs [ 7 , 10 , 12 , 13 ]. We presume that this form of abuse is captured by one of the seven questions; that is, “Did something happen that scared you so much that you thought about it for years after?” Second, retrospective assessment of childhood experiences may be subject to errors, inconsistencies, and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Our study does have a number of limitations. First, our childhood adversity measure does not contain an item specific to sexual abuse, a critically important adverse childhood experience known to be more prevalent in women, MSM, and people who use drugs [ 7 , 10 , 12 , 13 ]. We presume that this form of abuse is captured by one of the seven questions; that is, “Did something happen that scared you so much that you thought about it for years after?” Second, retrospective assessment of childhood experiences may be subject to errors, inconsistencies, and recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have indicated a link between socioeconomic status and GBV [98][99][100], GBV is by no means confined to people living in poverty. Incarceration [101], minority [24,52,60,102] and migrant [103] status or relocation [104] are similarly linked, as is substance abuse [105,106], or a co-occurrence of these contexts [107][108][109]. Almost all of these studies are from the United States.…”
Section: Transactional Sexmentioning
confidence: 95%
“…Housing instability on reservations sometimes results in migration to urban areas, leaving young women vulnerable to prostitution. Although AI/AN people constitute only 1% of adults and 2% of youth in Minnesota, they constitute 11% of homeless adults and 20% of homeless youth (Koepplinger, 2009 (Farley, Lynne & Cotton, 2005;Kingsley & Mark, 2000;McKeown, Reid, & Orr, 2004), just as Māori youth in New Zealand (Plumridge & Abel, 2001) and Atayal youth in Taiwan (Hwang & Bedford, 2003) are overrepresented in prostitution.…”
Section: Continued On Next Pagementioning
confidence: 99%